INFLUENCE OF LIVE STREAMING SHOPPING FEATURE ON PURCHASE INTENTION FOR LOCAL BEAUTY BRAND THROUGH EMOTIONAL FACTORS IN THE S-O-R MODEL - Kadiva Dwilia Rosadiputri; Indira Rachmawati (PT. Jurnal Center Indonesia Publisher, 2025)
The phenomenon of online shopping has driven business players to be more innovative in promoting their products on existing digital platforms. There is a technological innovation that allows online businesses to showcase and demonstrate their products in real-time, known as live streaming shopping. TikTok has become one of the popular social-commerce platforms with beauty content within its application. This study aims to better understand the influence of TikTok live streaming shopping on the purchase intention of the local beauty brand through emotional factors. We applied the S-O-R (Stimulus, Organism, Response) model, with influencer credibility variables added to the emotional factors in the S-O-R model. Data were collected from 300 respondents who registered through a Google Form survey with predetermined criteria. PLS-SEM using Smart PLS was chosen for data analysis. The study revealed that attraction, cognitive assimilation, and influencer credibility mediate the relationship between real-time interaction, shopping guidance, visibility, media richness, and consumer purchase intention. Therefore, live streaming shopping through emotional factors significantly influences consumers' purchase intention. This research found that the enrichment of material living standards has transformed people’s purely demand-oriented shopping style. This study result help enterprises to better apply live streaming more effectively and expanding channels promotion strategies.